The Impact of Paternalistic Leadership Approach on Employees’ Performance and Organizational Identification - ÇALAN, Mahsum; AKSU, Akın (Turizam, 2024)
The present study aims to investigate the effect of paternalistic leadership on the performance and organizational identification of employees.The research has adopted the quantitative approach and data collected from population comprised employees in five star accommodation establishments located in Antalya.In order to represent the research population,the convenience sampling method was used to determine the sample,and in 2021 summer season 380 questionnaires obtained from the sample were analysed.Pearson correlation analysis was used to determine the relationship between the scale variables.According to the results,a positive and significant relationship was found between the paternalistic leadership perception,and employee performance and organizational identification.Paternalistic leadership perception explained 6% of the change in employee performance.In addition,paternalistic leadership behaviour explained 11.1% of the variance of organizational identification.Significant and positive relationship were found between the subdimension of paternalist leadership (creating a family environment (t=3.073,p≤.01),expectation of loyalty and deference (t=2.061,p≤.05)) and organizational identification.And another positive relation was found between sub dimension of paternalist leadership (creating a family environment at workplace (t=2.328,p≤.05)) and performance.This research will be the first study in the tourism sector in Turkey in terms of paternalistic leadership,employee performance and organizational identification.Since there is no other study in the literature in which these three variables are investigated together in the field of tourism,it will fill the gap in the research area.
Keywords: Paternalistic Leadership,Employee Performance,Organizational Identification,Tourism Sector,Accommodation Organizations,Antalya